FAMILY-BASED CARE USING THE OREM SELF-CARE MODEL IN FAMILIES WITH HYPERTENSION: A CASE STUDY - Muhamad Gustaf Al Fajar; Desy Indra Yani; Nina Sumarni (Universitas Airlangga, 2024)
Introduction: Uncontrolled hypertension can negatively affect a person's physical well-being and quality of life. The implementation of family-based care helps families to achieve independence in maintaining family health. The Orem model approach can explain how the family's role in caring for family health independently. Objectives: This study aims to describe the application of family-based care with the Orem model approach in hypertensive families. Methods: This research was conducted with a case study approach, using a nursing process consisting of assessment with the Orem model, namely assessment of basic conditional factor data, strength components, universal self care, developmental self care, and health deviation and Hypertension Self Management Behavior (HSMB), formulation of nursing diagnoses using SDKI, nursing plans using SIKI, implementation and evaluation. Results: Intervention and implementation were carried out for four meetings including providing family-based health education using leaflet media, foot massage modality therapy and self-management monitoring sheets. The results obtained by both families experienced an increase in behavioral self-management scores and controlled blood pressure. Conclusions: Family-based care can improve behavioral self-management in compliant families.